Pemanfaatan Egrang Batok Kelapa Untuk Meningkatkan Kecerdasan Kinestetik Anak dan Menumbuhkan Minat Terhadap Permainan Tradisional - Salsabila Anjas Parastuti; Rif’atul Husnah; Muhammad Nur Hasan (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This research was motivated by the abundance of coconut shell waste in Lamongan and the decreased interest of children in traditional games. Therefore, this research is done intending to discover the utilization of coconut shell waste as egrang to increase children’s kinesthetic intelligence and to grow interest in traditional games. The method used in this study is experimental design, with data collection techniques in the form of observation and documentation in 12 children in group A of TK 02 Mazro’atul Ulum Paciran. In developing kinesthetic intelligence using the traditional game of egrang by teaching children group A kindergarten 02 Mazro’atul Ulum Paciran how to make egrang from coconut shell and doing activities to play egrang together. Based on observations, mentoring, data collection, and the results of tests that have been carried out, it can be concluded that there is a significant effect of playing egrang to increase kinesthetic intelligence and foster interest in traditional games in children in group A of TK 02 Mazro'atul Ulum Paciran Lamongan. Where the independent sample t-test results obtained with a probability value of p-value <0.05 and a t-value of 12.457 which is in the H0 area is rejected.